Reconfiguration modulation strategy analysis for proactive adaptability of the monitored inverter to on-line monitoring system of IGBT modules. (December 2020) - Ma, Mingyao; Guo, Weisheng; Zhan, Mingyue; Yang, Shuying; Li, Fei
Abstract: To realize on-line monitoring for insulated-gate bipolar transistor (IGBT) modules in the three-level neutral point clamped (NPC) inverters, a reconfiguration modulation strategy is proposed. The saturated voltage drop (VCE) is one of the most common diagnostic signs of IGBTs' healthy status due to the advantages of monitoring method such as simple theory, mature implementation, and accurate measurement, and the method to extract VCE in the monitoring system has been researched in the previous study. On this basis, considering realizing on-line monitoring process, essential supported hardware and proactive on-line monitoring environment are needed to guarantee the safe and friendly on-line monitoring implementation. Analysis has been made to show that the on-line monitoring system is able to work regularly by just making use of the inherent O state of a three-level NPC inverter in some circumstances. But to guarantee the monitoring process and the safety of the monitored NPC inverter, the novel reconfiguration strategy is a kind of necessary and essential means to create an on-line monitoring environment, and it is proposed and researched in this paper. Through theoretical derivation, the optimization of reconfiguration strategy is obtained. The reconfiguration strategy proposed in this research has been achieved and its validity is proved based on experimental results.